(8r-23)=(6r+15)

Simple and best practice solution for (8r-23)=(6r+15) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8r-23)=(6r+15) equation:



(8r-23)=(6r+15)
We move all terms to the left:
(8r-23)-((6r+15))=0
We get rid of parentheses
8r-((6r+15))-23=0
We calculate terms in parentheses: -((6r+15)), so:
(6r+15)
We get rid of parentheses
6r+15
Back to the equation:
-(6r+15)
We get rid of parentheses
8r-6r-15-23=0
We add all the numbers together, and all the variables
2r-38=0
We move all terms containing r to the left, all other terms to the right
2r=38
r=38/2
r=19

See similar equations:

| 180=45+(-3x)+(15-x) | | 6j+11j+10j=-14 | | 6+3/4x=1/2x-45. | | 8b-6=6b+2 | | 40=8t+8 | | 17j-13j=20 | | 3x+15;x=9 | | 16m+-13m-m=10 | | 10r^2-1=9 | | 40=8t-8 | | 11u-6u+3u+2u=10 | | 6(x×5)=42 | | x+7(5x+12)=48 | | X+x+3=3+2x+6 | | 18+2-3x=7x | | 130=10r | | 14b=−56+7b−32 | | 6/4y+1=9/9y-6 | | w+14=34 | | 6x-11=3x+19x= | | 18x+72=-18x | | 9(x-2)+4=58 | | -1=-3+b/9 | | 16*w=400 | | 2.v-10=12 | | 18g=4g | | 6=11-g | | 180=70+(1+3x)+(-3+5x) | | t/42=16 | | ((2x-3)-1)=4 | | 3/1/4x+1=2x | | 10a–5=85 |

Equations solver categories